Question Answering in Webclopedia - Hovy, Eduard; Gerber, Laurie; Hermjakob, Ulf; Junk, Michael; Lin, Chin-Yew (The Ninth Text REtrieval Conference (TREC 9), 2000)
In this paper we describe the Webclopedia, a system that uses a classification of QA types to facilitate coverage, uses a robust syntactic-semantic parser to perform the analysis, and contains a matcher that combines word- and parse-tree-level information to identify answer passages. Section 2 outlines the Webclopedia approach and architecture; Section 3 describes document retrieval and processing, Section 4 describes the QA Typology, Section 5 the parsing, and Section 6 the matching.